Capturing the non-technical skills of a technical skills trainer (NTS-TeST) during simulation. Issue 3 (August 2021) - Pears, Matthew; Biyani, Chandra Shekhar; Joyce, Adrian D; Spearpoint, Ken; Yiasemidou, Marina; Cleynenbreugel, Ben Van; Patterson, Jake; Mushtaq, Faisal
Objective: To develop an assessment instrument that can be used as a comprehensive feedback record to convey to a trainer the non-technical aspects of skill acquisition and training. Methods: The instrument was developed across three rounds. In Round 1, 6 endourological consultants undertook a modified Delphi process. Round 2 included 10 trainers who assessed each question's relevance and practicability. Round 3 involved a pilot study with fifteen urology residents who participated in a technical skills simulation session with the incorporation of the instrument. We report the content, face, and construct validity, and the internal consistency of an NTS instrument for trainers. Results: The instrument had a consistent and a high positive average for each of the 4 sections of the instrument, regardless of the type of user. Positive Spearman's correlation coefficients (0.02 to .64) for content validity and Cronbach's alpha (a = 0.70) indicated good validity and moderate reliability of the instrument. Conclusion: We propose a novel NTS instrument for trainers during a simulation. This instrument can be used for benchmarking the quality of technical skills simulation training.